SUITABILITY OF ICE STORED MACKEREL AND SARDINE FOR CANNING - MADHAVAN, P; BALACHANDRAN, K K; CHOUDHURI, D R (Fishery Technology, 2025)
The paper reports the re~ults of studies. on ice storage andsubsequent canning of mackerel (Rastrelliger l